Characteristics of Senile Cataract Patients Treated at Agoesdjam Hospital Ketapang February-April 2025: A Descriptive Cross-Sectional Study - Angelina, Maria; Manoe, Helen Anastasia (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2025)
Introduction: Senile cataract is opacification of the crystalline lens and can occur with increasing age. This study aims to discover the characteristics of senile cataract patients at Agoesdjam Hospital. Methods: This is a descriptive study with a cross-sectional approach. Data were taken from medical records of patients with the diagnosis of cataract at Agoesdjam Hospital in February-April 2025. Result: A total of 164 senile cataract patients and 294 eyes with cataract had been examined at Agoesdjam Regional Hospital with majority of patients were female (51.2%). Senile cataracts were found mostly in the 56-65 years age group (37%), came from Delta Pawan District (31.09%), and were diagnosed at the immature cataract stage (67.6%). From 164 patients, 15.2% of patients have diabetes mellitus and 46.9% of patients have hypertension. Conclusion: Senile cataracts at Agoesdjam Hospital were mostly found in female patients, in the age group of 56-65 years old, living in Delta Pawan District, at the immature cataract stage, have history of diabetes mellitus and hypertension. The result of this research highlights the importance of early detection of cataract to optimize treatment outcome.